Robust Vehicular Communications Using the Fast-Frequency-Hopping-OFDM Technology and the MIMO Spatial Multiplexing - Hamarsheh, Qadri; Daoud, Omar Rawhi; Al-Akaidi, Marwan; Damati, ahlam; Bani Younis, Mohammed (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
Vehicle-to-Vehicle communication is one of the more emerging technologies in the 21st century from either the comfortable transportation or safer transportation point of view. Vehicle-to-Vehicle communication has one crucial factor, which is the huge information to be shared among vehicles, such as the position, the road data. In such situation, the accurate information sharing process is the most important factor in order to make the vehicles operating in the most feasible way. This work proposes a more robust vehicle communication system to make the existing vehicle transportation system more efficient. In this paper, we propose a fast frequency hopping orthogonal frequency division multiplexing to mitigate the Doppler spread effect on our previously published clustering benchmark. This benchmark contains both of a clustering weighting factor based stage and a multiparallel processing stage. This is in addition to modify the PHY layer of the existing IEEE 802.11p standard in order to impose Multiple Input Multiple Output for higher throughput purposes. The results show a noticeable stability compared to our previously published work. Furthermore, the results are almost exceeds the achieved results from the Lower-ID Distributed Clustering Algorithm (DCA) from both of the speed and communication range.